2020
DOI: 10.3390/antiox9060541
|View full text |Cite
|
Sign up to set email alerts
|

Edible Leafy Plants from Mexico as Sources of Antioxidant Compounds, and Their Nutritional, Nutraceutical and Antimicrobial Potential: A Review

Abstract: A review of indigenous Mexican plants with edible stems and leaves and their nutritional and nutraceutical potential was conducted, complemented by the authors’ experiences. In Mexico, more than 250 species with edible stems, leaves, vines and flowers, known as “quelites,” are collected or are cultivated and consumed. The assessment of the quelite composition depends on the chemical characteristics of the compounds being evaluated; the protein quality is a direct function of the amino acid content, which is ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 113 publications
(168 reference statements)
0
19
0
9
Order By: Relevance
“…Among all plant organs, leaves are the largest accumulators of bioactive compounds, such as secondary metabolites. Several recent studies reported phytochemical profiles and biological activities of leaf extracts of various cultivated plants [ 2 , 4 , 5 , 6 ]. Hence, although plant leaves are considered as agricultural waste, they are a rich source of high-value nutra-pharmaceutical compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Among all plant organs, leaves are the largest accumulators of bioactive compounds, such as secondary metabolites. Several recent studies reported phytochemical profiles and biological activities of leaf extracts of various cultivated plants [ 2 , 4 , 5 , 6 ]. Hence, although plant leaves are considered as agricultural waste, they are a rich source of high-value nutra-pharmaceutical compounds.…”
Section: Introductionmentioning
confidence: 99%
“…These edible plants provide the totonac and nahua diet with fibre, carbohydrates, vitamins, and minerals, as well as antioxidants [ 20 , 91 , 92 ]. Quelites, the name given to edible plants in the Sierra Norte de Puebla are plants that form part of the indigenous food system, the leaves are generally consumed, and their occurrence depends on the climate of the region, which has altitudes ranging from 200 to 2000 m above sea level.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…Furthermore, microbial inhibition could contribute to solving one of the major global public health risks, i.e., the emergence of multi-drug-resistant bacterial strains in the food chain that could cause foodborne microbial-resistant diseases [ 21 ]. Thus, the valorization of olive leaves, a massive agricultural by-product, is possible through their application in nutraceutical foods and supplements, as has been proposed by several authors in recent years, since plant leaves are currently the main waste product of the agricultural industry, and can become a major environmental problem and cause of pollution [ 22 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%